High-performance photocatalytic metal organic framework antibacterial material as well as preparation method and application thereof
By growing a metal organic frame of cerium elements on a single layer of graphene oxide and loading arginine, a high-performance photocatalytic MOF antibacterial material is solved, and efficient killing of bacteria is achieved Anti-and wound healing effects.
Patent Information
- Application Number
- CN202411497171.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-18
AI Technical Summary
The visible light response of existing photocatalytic antibacterial materials is weak and the electrons and holes are recombined quickly, resulting in insufficient photocatalytic antibacterial efficiency. Most hydrogel wound dressings have a single function, and antibacterial performance needs to be further improved.
The metal organic framework (UiO 66) with cerium element (Ce) as the metal node grew in situ on a single layer of graphene oxide and was loaded with small arginine molecules to form a high-performance photocatalytic MOF antibacterial material (UiO66@GO@arg ). This material produces reactive oxygen species through photocatalytic action under light, significantly improving the antibacterial effect, and forms a nano-hydrogel dressing with chitosan with a stable three-dimensional structure.
Efficient killing of E. coli and Staphylococcus aureus was achieved, with a bactericidal rate of more than 95%. It was proved in animal experiments that it can effectively promote wound healing and skin tissue regeneration.
Smart Images

Figure CN119456031A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal organic frameworks, and in particular relates to a high-performance photocatalytic metal organic framework antibacterial material and a preparation method and application thereof. Background Art
[0002] Microbial infection seriously threatens human health. The abuse of antibiotics and the emergence of "super bacteria" are a thorny global public health problem. By 2050, the total number of deaths due to antibiotic resistance worldwide is expected to rise to 10 million per year, which has caused immeasurable negative impacts on the social economy. According to the US Centers for Disease Control and Prevention, antibiotic resistance causes economic losses of up to US$55 billion each year, which has become the most worrying public health issue in the 21st century. As the first immune barrier of the human body, the skin is extremely susceptible to invasion by pathogenic microorganisms, causing wound infection. In severe cases, it can cause tissue necrosis, sepsis and even life-threatening. At present, the clinical treatment of wound infection mainly focuses on local debridement combined with systemic antibiotic treatment. Therefore, the development of new antibacterial materials and wound dressings is urgent.
[0003] Hydrogel is a type of extremely hydrophilic three-dimensional network structure polymer material. According to the source of the polymer, it can be divided into natural polymers, such as alginate, chitosan, pectin, cellulose, etc.; and synthetic polymers such as polyvinyl alcohol (PVA), polyethylene oxide (PEO) and polyethylene glycol (PEG). Due to its soft texture, variable shape, high water absorption and biocompatibility, it has been widely used in wound dressings. However, most reported hydrogel wound dressings have a single function, and their antibacterial properties also need to be further improved. How to compound multifunctional antibacterial materials in hydrogels needs further exploration.
[0004] Photocatalytic antibacterial materials have become promising biocides due to their ability to generate reactive oxygen species (ROS) under irradiation. However, most commercially available photocatalytic antibacterial agents, such as TiO2-based materials, require high-energy ultraviolet (UV) light to generate ROS. Although some photocatalysts for visible light catalysis have been developed, the antibacterial efficiency of these materials still needs to be improved before they can be widely adopted. Metal-organic frameworks (MOFs) are an emerging type of porous crystalline materials constructed by metal ions and organic ligands in the form of coordination bonds. MOFs have the characteristics of porosity, large specific surface area, and multiple metal sites, so they have unique advantages in adsorption, photocatalysis, biomedical materials, etc. Especially in the aspect of photocatalytic antibacterial / antiviral, compared with traditional metal oxides, MOFs have the following advantages: ① Rational design of organic ligands can adjust the material's visible light absorption spectrum; ② Organic ligands can effectively separate metal nodes, thereby improving the utilization of active sites; ③ The porous and large specific surface area structure is conducive to the diffusion of reactive oxygen, thereby improving the efficiency of generating reactive oxygen.
[0005] When applied to the field of photocatalytic antibacterial treatment, most MOF materials have the disadvantages of weak visible light response and fast recombination of generated electrons and holes, resulting in insufficient photocatalytic antibacterial efficiency. In order to improve the photocatalytic efficiency of MOF, researchers have further adopted different methods such as metal ion doping, loading photosensitizers and combining with other semiconductor materials. For example, introducing photosensitizers as ligands in the structure of MOF can avoid the self-quenching phenomenon of photosensitizers and give MOF new properties. Therefore, Luo et al. synthesized porphyrin-doped MOF materials (PB@MOF). Porphyrin as a photosensitizer can accelerate the transfer of photoexcited electrons, thereby significantly improving the photocatalytic antibacterial effect of MOF. Wang et al. encapsulated quantum dots in ZIF-8. Compared with ZIF-8 alone, QDs@ZIF-8 nanocomposites showed better antibacterial activity under visible light irradiation. However, the above-mentioned MOF-based photocatalytic antibacterial materials have a single function, and the photocatalytic antibacterial efficiency needs to be further improved. Therefore, it remains a huge challenge to develop MOF-based antibacterial materials with high antibacterial properties and promote wound healing, and to prepare multifunctional gel wound dressings based on them. Summary of the invention
[0006] In view of the above problems, the object of the present invention is to provide a high-performance photocatalytic metal-organic framework antibacterial material and a preparation method and application thereof.
[0007] The technical contents of the present invention are as follows:
[0008] The present invention provides a method for preparing a high-performance photocatalytic metal organic framework antibacterial material, comprising the following steps:
[0009] Dissolve terephthalic acid (H2BDC) and ammonium cerium nitrate (Ce(NH4)2(NO3)6) respectively and mix them evenly, add the monolayer graphene oxide dispersion, stir and mix well, and then heat to react. After the reaction is completed, cool to room temperature, add arginine, and stir and react in the dark. After the reaction is completed, collect the precipitate by centrifugation, wash it, and dry it to obtain GO-UiO66@arg powder;
[0010] The mass ratio of terephthalate to ammonium cerium nitrate acid is 1:(3-5); preferably 1:3.3;
[0011] The phthalic acid is dissolved in an organic solution, the organic solution includes a dimethylformamide solution, and the solid-to-liquid ratio of the phthalic acid to the organic solution is (25-40): 1 mg / mL;
[0012] The ammonium cerium nitrate is dissolved in deionized water, and the solid-liquid ratio of the ammonium cerium nitrate to the deionized water is (200-300): 1 mg / mL;
[0013] The heating reaction temperature is 150°C to 200°C and the time is 15 to 30 minutes;
[0014] The use concentration of the monolayer graphene oxide dispersion is 3 to 8 mg / mL, preferably 5 mg / mL;
[0015] The concentration of arginine is 10-30 mg / mL, preferably 20 mg / mL;
[0016] The stirring reaction temperature is 100°C to 180°C, and the time is 15 to 30 minutes;
[0017] The washing reagents include anhydrous ethanol, deionized water and DMF.
[0018] The present invention also provides an application of a high-performance photocatalytic metal organic framework antibacterial material. The metal organic framework antibacterial material obtained by the above preparation method is used to prepare wound care dressings, including antibacterial hydrogel dressings, etc.
[0019] The preparation of the antibacterial hydrogel dressing comprises: dissolving quaternized chitosan, adding acrylamide polymer, GO-UiO66@arg and a cross-linking agent, stirring evenly, adding an initiator and a catalyst, and standing at room temperature to obtain an antibacterial hydrogel dressing based on a metal organic framework material;
[0020] The preparation method of the quaternary ammonium chitosan comprises the following steps: dissolving chitosan in deionized water, adding glacial acetic acid for heating reaction, then adding a cationizing agent, continuing stirring and heating reaction, then centrifuging, collecting the supernatant, fully dialyzing it with deionized water, and freeze-drying to obtain the quaternary ammonium chitosan;
[0021] The solid-liquid ratio of chitosan to deionized water is (35-40):1 mg / mL, and the preferred ratio is 1:36 (mg / mL);
[0022] The amount of glacial acetic acid is 150-200 μL (0.5% v / v), preferably 180 μL;
[0023] The cationizing agent includes glycidyl trimethylammonium chloride (GTMAC), the dosage of which is 10-20 mg / mL, preferably 15 mg / mL, and its function is to quaternize chitosan;
[0024] The temperature of the heating reaction is 45° C. to 70° C., and the time is 12 to 24 hours.
[0025] The acrylamide polymer includes one or more of poly-N-isopropylacrylamide (PNIPAm) and poly(acrylic acid-N-isopropylacrylamide) copolymer, and the concentration thereof is 40-60 mg / mL;
[0026] The cross-linking agent includes one or more of N,N'-methylenebisacrylamide (DMAA) and polyethylene glycol diacrylate (PEGDA), and the concentration thereof is 1 to 2 mg / L;
[0027] The initiator includes one or more of ammonium persulfate (APS) and potassium persulfate (KPS), and the concentration thereof is 4 to 6 mg / mL;
[0028] The catalyst includes one or more of tetramethylethylenediamine (TEMED) and triethylenetetramine (TETA), and the concentration thereof is 0.5 to 1.5 μL / mL;
[0029] The standing time at room temperature is 10 to 25 minutes.
[0030] The beneficial effects of the present invention are as follows:
[0031] The high-performance photocatalytic metal-organic framework antibacterial material of the present invention is a metal-organic framework (UiO 66) with cerium (Ce) as a metal node, which is then in situ grown on a monolayer of graphene oxide (UiO 66@GO), and arginine small molecules are loaded in the MOF framework to obtain a high-performance photocatalytic MOF antibacterial material (UiO66@GO@arg). Under light, (UiO66@GO@arg can produce active oxygen through photocatalysis, thereby playing an antibacterial role, and has a killing effect on Escherichia coli (EC) and Staphylococcus aureus (SA);
[0032] And the MOF material UiO66@GO@arg of the present invention is combined with chitosan to form a nano hydrogel with a stable three-dimensional structure, and it is used as a wound dressing for antibacterial treatment; the Ce-based MOF composite QCS / GO-UiO 66@arg / PNIPAm hydrogel prepared by the present invention has excellent elasticity, adhesion, water absorption and biocompatibility and other properties; and under light, it has excellent photocatalytic bactericidal effect, and has a good killing effect on Escherichia coli and Staphylococcus aureus. In addition, animal experiments have proved that QCS / GO-UiO 66@arg / PNIPAm hydrogel can effectively promote the healing of mouse wounds and the regeneration of skin tissue. The specific advantages mainly include the following three aspects: 1) UiO 66@GO doped with graphene oxide has excellent Ce 3+ / Ce 4+ 1) The mixed valence state of UiO 66@GO@arg exhibits excellent photocatalytic antibacterial effect; 2) The arginine loaded therein can be decomposed and released nitric oxide (NO) under the catalysis of nitric oxide synthase (Inducible Nitric Oxide Synthase, referred to as iNOS) and hydrogen peroxide (H2O2) produced by bacteria, which has the effect of promoting cell proliferation and wound healing; 3) The hydrogel dressing can better fit the skin wound, absorb tissue exudate, keep the wound environment dry, and further inhibit the growth of bacteria. The research results show that the UiO 66@GO@arg prepared by the present invention has excellent photocatalytic antibacterial properties. The hydrogel prepared based on this can achieve a sterilization rate of Escherichia coli and Staphylococcus aureus of more than 95% under light. The present invention provides a new research idea and application prospect for the development of gel materials with both antibacterial and tissue repair functions. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The SEM image and XRD pattern of GO-UIO-66@arg material;
[0034] Figure 2 Evaluation diagram of the antibacterial effect of GO-UiO 66@arg materials with different concentrations on Escherichia coli and Staphylococcus aureus;
[0035] Figure 3 The intuitive picture and scanning electron microscopy image of QCS / GO-UiO 66@arg / PNIPAm hydrogel;
[0036] Figure 4 Mechanical properties analysis diagram of QCS / GO-UiO 66@arg / PNIPAm hydrogel;
[0037] Figure 5 The antibacterial effect evaluation results of QCS / GO-UiO 66@arg / PNIPAm hydrogel (a: Escherichia coli, b: Staphylococcus aureus);
[0038] Figure 6 Pictures of wound healing in mice in different hydrogel groups (scale bar: 0.5 cm);
[0039] Figure 7 Analysis of wound healing in mice in different hydrogel groups (*P<0.05). DETAILED DESCRIPTION
[0040] The present invention is further described in detail below through specific implementation cases and accompanying drawings. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of protection of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art are all within the scope of the claims attached to this application.
[0041] Unless otherwise specified, all raw materials and reagents of the present invention are raw materials and reagents from the conventional market.
[0042] Example 1
[0043] A high-performance photocatalytic metal-organic framework antibacterial material
[0044] 1) Preparation of GO-UiO66@arg:
[0045] Dissolve 106.2 mg of terephthalic acid (H2BDC) in 3.6 mL of dimethylformamide (DMF) to obtain solution ①;
[0046] Dissolve 350.1 mg of cerium ammonium nitrate (Ce(NH4)2(NO3)6) in 1.2 mL of deionized water to obtain solution ②;
[0047] Mix solution ① and solution ② evenly and add them into a round-bottom flask. Then add 2 mL of monolayer graphene oxide dispersion (concentration 5 mg / mL). Put the round-bottom flask into a 120°C oil bath and heat for 15 minutes.
[0048] After the reaction was completed, the mixture was cooled to room temperature, and the product was washed by centrifugation with DMF, anhydrous ethanol, and deionized water. An excess of L-arginine was further added and stirred for 6 hours in the dark. After the reaction was completed, the mixture was washed by centrifugation with deionized water, freeze-dried, and sieved to obtain a powder, which was stored in a refrigerator at 4°C.
[0049] GO-UiO66@arg was characterized by scanning electron microscopy (SEM). Figure 1 As shown in the left figure, UiO 66 was observed to be round particles with a particle size of about 300nm, while GO-UiO66@arg was UiO 66 particles attached to a layer of graphene oxide (GO) film. The metal organic framework structure was further determined by powder diffraction test (XRD) data, and both GO-modified and L-arg-loaded nanoparticles showed similar XRD patterns to UiO66 nanoparticles ( Figure 1 Right), indicating that the crystal structure of the nanoparticles remains almost unchanged after functionalization. In summary, GO-UiO66@arg was successfully prepared in this example;
[0050] The antibacterial properties of GO-UiO66@arg were further evaluated, and the results were as follows Figure 2 As shown in the figure, under light conditions, with the increase of the concentration of GO-UiO66@arg material, its antibacterial effect is significantly improved. When the concentration is 150 μg / mL, its antibacterial rate against Escherichia coli (left picture) and Staphylococcus aureus (right picture) is more than 95%, which is significantly different from the control group (**P<0.01). It can be seen that the prepared GO-UiO66@arg has excellent photocatalytic antibacterial properties.
[0051] Example 2
[0052] Preparation of a metal organic framework-based gel antibacterial dressing
[0053] Weigh 1g chitosan and dissolve it in 36mL deionized water, add 180μL glacial acetic acid (0.5% v / v) and mix it evenly by ultrasonication, and react it in an oil bath at 55℃ for 30 minutes; then add 610mg glycidyl trimethylammonium chloride (GTMAC) and continue to react at 55℃ for 18 hours. Then centrifuge for 20 minutes, collect the supernatant and put it into a dialysis bag (MWCO 3500), dialyze it in a deionized water solution for 3 days, and freeze-dry it to obtain quaternized chitosan (QCS);
[0054] QCS with a mass ratio of (1.5wt%) was dissolved in PBS (pH=7.4), and poly (N-isopropylacrylamide) (PNIPAm) (50mg / mL), GO-UiO 66@arg (500mg / mL), and cross-linker N,N'-methylenebisacrylamide (DMAA) (1.5mg / L) were added and stirred thoroughly. Then, initiator ammonium persulfate (APS) (5mg / mL) and catalyst tetramethylethylenediamine (TEMED) (1.0μL / mL) were added and allowed to stand at room temperature for ten minutes to form a hydrogel based on GO-UiO66@arg.
[0055] The structure and properties of the prepared GO-UiO66@arg-based hydrogel QCS / GO-UiO66@arg / PNIPAm were tested as follows:
[0056] The structure of the synthesized GO-UiO66@arg-based hydrogel QCS / GO-UiO66@arg / PNIPAm is shown in Figure 3 As shown, it has a stable three-dimensional mesh gel structure and is extremely hydrophilic. Scanning electron microscopy shows that there are many loose pores inside it, and the GO-UiO66@arg material is attached to the pores.
[0057] The mechanical properties of the hydrogel QCS / GO-UiO66@arg / PNIPAm were further characterized by elastic modulus experiments using a tensile machine, such as Figure 4((a) Elasticity analysis of QCS / GO-UiO66@arg / PNIPAm hydrogel; (b) Adhesion analysis of QCS / GO-UiO66@arg / PNIPAm hydrogel; (c) Swelling performance analysis of QCS / GO-UiO66@arg / PNIPAm hydrogel; Equilibrium swelling ratio of hydrogel ESR = Ws / Wd, Ws is the weight of hydrogel after swelling equilibrium (24h); Wd is the dry weight of gel (0h)) As shown in Figure a, it can be seen that the maximum tensile force that the hydrogel can withstand is 40.09kPa and the maximum strain reached is 49%. In addition to excellent elastic properties, the hydrogel has good adhesion due to its colloidal texture. The two ends of the QCS / GO-UiO66@arg / PNIPAm hydrogel are respectively covered on fresh pig skin (simulating normal human skin tissue), and the maximum adhesion before the contact surface separation is measured by a tensile machine, which is 25.55kPa (Figure b). At the same time, due to its loose network structure and rich hydrophilic groups, QCS / GO-UiO 66@arg / PNIPAm hydrogel exhibits excellent swelling properties. After freeze-drying an appropriate amount of QCS / GO-UiO 66@arg / PNIPAm hydrogel, it was soaked in water for 24 hours, and its equilibrium swelling ratio (weight of hydrogel after swelling equilibrium / gel dry weight) was 4.38. The above results prove that the hydrogel based on GO-UiO 66@arg was successfully prepared (Figure c).
[0058] The antibacterial effect of the hydrogel QCS / GO-UiO66@arg / PNIPAm was further evaluated by adding Figure 5 As shown in the figure, compared with the gel without GO-UiO 66@arg material, QCS / GO-UiO 66@arg / PNIPAm hydrogel exhibits excellent antibacterial advantages and has a good inactivation effect on Escherichia coli and Staphylococcus aureus under light conditions.
[0059] To further evaluate the anti-inflammatory, antibacterial and wound healing abilities of QCS / GO-UiO66@arg / PNIPAm hydrogel, a mouse skin wound model was constructed and the mice were randomly divided into four groups, with five mice in each group. They were: 1) blank control group (no additional treatment); 2) blank hydrogel group (QCS / PNIPAm hydrogel); 3) material hydrogel group (QCS / GO-UiO66@arg / PNIPAm hydrogel); 4) material hydrogel group + light (QCS / GO-UiO66@arg / PNIPAm hydrogel + sunlight) group; then a wound with a length of about 1 cm was formed on the skin of each mouse, and different hydrogel dressings were covered on the wound surface and fixed; each group changed the hydrogel dressing every other day; the light-exposed group was exposed to simulated sunlight for half an hour after the dressing change. By measuring the wound length of the mice on the 3rd, 7th and 14th days, the wound conditions of each group were improved compared with the 0th day.
[0060] The results are as follows Figure 6 As shown, compared with the blank control group and the blank hydrogel group (QCS / PNIPAm hydrogel), the wound healing of mice in the material hydrogel group (QCS / GO-UiO66@arg / PNIPAm hydrogel) was the best, and under light conditions, the wounds were basically healed after 14 days, and the results were statistically significant (*P<0.05)( Figure 7 ).
[0061] Example 3
[0062] A high-performance photocatalytic metal-organic framework antibacterial material
[0063] 1) Preparation of GO-UiO66@arg:
[0064] Dissolve 109 mg of terephthalic acid (H2BDC) in 3.5 mL of dimethylformamide (DMF) to obtain solution ①;
[0065] Dissolve 340 mg of cerium ammonium nitrate (Ce(NH4)2(NO3)6) in 1.5 mL of deionized water to obtain solution ②;
[0066] Mix solution ① and solution ② evenly and add them into a round-bottom flask. Then add 2.5 mL of monolayer graphene oxide dispersion (concentration 5 mg / mL). Put the round-bottom flask into a 120°C oil bath and heat for 15 minutes.
[0067] After the reaction was completed, the mixture was cooled to room temperature, and the product was washed by centrifugation with DMF, anhydrous ethanol, and deionized water. An excess of L-arginine was further added and stirred for 6 hours in the dark. After the reaction was completed, the mixture was washed by centrifugation with deionized water, freeze-dried, and sieved to obtain a powder, which was stored in a refrigerator at 4°C.
[0068] Example 4
[0069] Preparation of a metal organic framework-based gel antibacterial dressing
[0070] Weigh 1g chitosan and dissolve it in 40mL deionized water, add 160μL glacial acetic acid (0.5% v / v) and mix it evenly by ultrasonication, and react it in an oil bath at 55℃ for 30 minutes; then add 650mg glycidyl trimethylammonium chloride (GTMAC) and continue to stir and react at 60℃ for 15 hours. Then centrifuge for 20 minutes, collect the supernatant and put it into a dialysis bag (MWCO 3500), dialyze it in a deionized water solution for 3 days, and freeze-dry it to obtain quaternized chitosan (QCS);
[0071] QCS with a mass ratio of (1.5wt%) was dissolved in PBS (pH=7.4), and poly(acrylic acid-N-isopropylacrylamide) copolymer (50mg / mL), GO-UiO66@arg (500mg / mL), and cross-linker polyethylene glycol diacrylate (PEGDA) (1.5mg / L) were added and stirred thoroughly. Then, initiator potassium persulfate (KPS) (5mg / mL) and catalyst triethylenetetramine (TETA) (1.0μL / mL) were added and allowed to stand at room temperature for ten minutes to form a hydrogel based on GO-UiO66@arg.
[0072] Although the description of the present invention has been quite detailed and has been described in particular with respect to several described embodiments, it is not intended to be limited to any of these details or embodiments or any particular embodiment, so as to effectively cover the intended scope of the present invention. In addition, the present invention is described above with the embodiments foreseeable by the inventors, and its purpose is to provide a useful description, and those non-substantial changes to the present invention that are not currently foreseen may still represent equivalent changes of the present invention.
Claims
1. A method for preparing a high-performance photocatalytic metal-organic framework antibacterial material, characterized in that: The steps include: Dissolve terephthalic acid H2BDC and cerium ammonium nitrate Ce(NH4)2(NO3)6 separately and mix them evenly, add the single-layer graphene oxide dispersion, stir and mix well, and then heat to react. After the reaction is completed, cool to room temperature, add arginine, and stir and react in the dark. After the reaction is completed, collect the precipitate by centrifugation, wash it, and dry it to obtain GO-UiO66@arg powder.
2. The method for preparing a high-performance photocatalytic metal organic framework antibacterial material according to claim 1, characterized in that: The mass ratio of the terephthalate to the cerium ammonium acid nitrate is 1: (3~5); The phthalic acid is dissolved in an organic solution, and the solid-liquid ratio of the phthalic acid to the organic solution is (25-40): 1 mg / mL; The ammonium cerium nitrate is dissolved in deionized water, and the solid-liquid ratio of the ammonium cerium nitrate to the deionized water is (200-300): 1 mg / mL.
3. According to the method for preparing a high-performance photocatalytic metal-organic framework antibacterial material according to claim 1, the concentration of the monolayer graphene oxide dispersion is 3 to 8 mg / mL. 4 . The method for preparing a high-performance photocatalytic metal-organic framework antibacterial material according to claim 1 , wherein the concentration of arginine used is 10 to 30 mg / mL.
5. Application of a high-performance photocatalytic metal-organic framework antibacterial material, characterized in that: The high-performance photocatalytic metal-organic framework antibacterial material is obtained by the preparation method according to any one of claims 1 to 6, and is used to prepare wound care dressings, including antibacterial hydrogel dressings.
6. The use of the high-performance photocatalytic metal organic framework antibacterial material according to claim 5, characterized in that: The preparation of the antibacterial hydrogel dressing comprises: dissolving quaternized chitosan, adding acrylamide polymer, GO-UiO66@arg and a crosslinking agent, stirring evenly, adding an initiator and a catalyst, and standing at room temperature to obtain an antibacterial hydrogel dressing based on a metal organic framework material.
7. The use of the high-performance photocatalytic metal organic framework antibacterial material according to claim 5, characterized in that: The preparation method of the quaternary ammonium chitosan comprises the following steps: dissolving chitosan in deionized water, adding glacial acetic acid for heating reaction, then adding a cationizing agent, continuing stirring and heating reaction, then centrifuging, collecting the supernatant, fully dialyzing it with deionized water, and freeze-drying to obtain the quaternary ammonium chitosan; The solid-liquid ratio of the chitosan to deionized water is (35-40):1 mg / mL.
8. The use of the high-performance photocatalytic metal organic framework antibacterial material according to claim 5, characterized in that: The amount of glacial acetic acid used is 150-200 μL (0.5% v / v), and the preferred amount is 180 μL.
9. The use of the high-performance photocatalytic metal organic framework antibacterial material according to claim 5, characterized in that: The cationizing agent includes glycidyl trimethylammonium chloride (GTMAC), and the amount used is 10-20 mg / mL.
10. The use of the high-performance photocatalytic metal organic framework antibacterial material according to claim 5, characterized in that: The acrylamide polymer includes one or more of poly-N-isopropylacrylamide (PNIPAm) and poly(acrylic acid-N-isopropylacrylamide) copolymer, and the concentration of the acrylamide polymer is 40-60 mg / mL.
Citation Information
Cited By
Difunctional aerogel based on MOF chitosan filler as well as preparation method and application of difunctional aerogel
CN121198176A
Antibacterial nano composite material and preparation method thereof
CN121220491A
Electrically controlled drug release metal organic framework based composite application as well as preparation method and application thereof
CN121371235A
PVA-GO-coated UiO-66-coated PMIA photo-thermal composite film as well as preparation method and application thereof
CN121490604A
Temperature-sensitive shrinkage hydrogel dressing with photo-thermal self-regulation function and preparation method
CN121754376A